MODEL PENINGKATAN MUTU PENDIDIKAN MELALUI SUPERVISI AKADEMIK BERBASIS WEB - Prihayuda Tatang Aditya; Bambang Ismanto (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2020)
Aims of this study explain 1) the process of implementing academic supervision that has been running in the city of Salatiga; 2) how to develop a web-based academic supervision model in improving the quality of education; 3) and find out the results of the effectiveness of web-based academic supervision models in improving the quality of education through limited trials. This type of research is Research and Development (R and D). This research development step uses the Borg and Gall model which is integrated with the PLOMP model. Data collection techniques using interviews and questionnaires. Data analysis techniques were obtained from interviews and analyzed using qualitative descriptive techniques according to Miles and Huberman consisting of data (1) data reduction; (2) data presentation; and (3) conclusions and verification. The results from the questionnaire are calculated to get an average value. Limited trials were conducted by 5 supervisors and 5 teachers with an average yield of 89.92% for supervisors in the excellent category and 89% for the excellent teacher category. Judging from the results of limited trials, this study was declared effective for use.